Collagen dressing with thermosensitive properties and preparation method thereof
By combining collagen with raw materials such as polyN-isopropyl acrylamide, amino acid modified carboxymethyl chitosan and nanoferrous silicate powder, collagen dressings with temperature sensitive properties were prepared, which solved the problem of low mechanical strength of existing dressings and achieved higher mechanical properties and good biocompatibility.
Patent Information
- Application Number
- CN202510160283.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-13
AI Technical Summary
The existing collagen dressings are not mechanically strong and cannot meet the requirements for use in areas with larger movements such as extra-articular skin.
Collagen dressings with temperature-sensitive properties were prepared by combining collagen with raw materials such as polyN-isopropyl acrylamide, amino acid modified carboxymethyl chitosan and nanoferrous ferrous silicate powder. The dressing can undergo a reversible phase change at body temperature, thereby improving its mechanical properties.
The prepared collagen dressing has good mechanical properties after film formation, which can meet the requirements for use in areas with larger movements such as external joints, and the raw materials have good biocompatibility and are not irritated to the skin.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of collagen dressings, and in particular relates to a collagen dressing with temperature-sensitive properties and a preparation method thereof. Background Art
[0002] Collagen dressing is a biomedical material whose main component is collagen. Collagen is a natural protein that is widely present in human skin, bones, muscles, blood vessels and other tissues, and plays an important structural and functional role. Collagen dressing has excellent biocompatibility and biodegradability, and is used for the treatment and repair of various wounds. It has the functions of promoting wound healing, relieving pain, and preventing infection.
[0003] Collagen dressings can promote wound healing and tissue regeneration by interacting with collagen on the wound surface. It can form a protective film to prevent bacteria and other microorganisms from invading the wound surface, while also absorbing secretions and exudates from the wound surface to keep the wound surface clean and dry. In addition, collagen dressings can also promote tissue repair and regeneration by releasing some bioactive substances, such as cytokines and growth factors, thereby accelerating wound healing. Therefore, collagen dressings are a safe and effective biomedical material.
[0004] Thermosensitive collagen dressing is a new type of biomedical material, the main component of which is thermosensitive collagen. It is thermosensitive, that is, it can undergo a reversible phase change at body temperature, thereby achieving response and regulation to the wound environment. The Chinese patent with announcement number CN107540744B points out that different raw materials have a great influence on the mechanical strength of gel dressings. Based on this, a thermosensitive hydrogel with mechanical strength particularly suitable for joint synovial repair is proposed. However, its mechanical properties are not ideal like most gel dressings, and it cannot meet the use requirements of parts with high activity such as skin outside joints. Summary of the invention
[0005] One of the purposes of the present invention is to provide a collagen dressing with temperature-sensitive properties to solve the problem of low mechanical strength of existing collagen dressings; the second purpose is to provide a method for preparing a collagen dressing with temperature-sensitive properties.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The collagen dressing with temperature-sensitive properties comprises the following raw materials by weight:
[0008] 1.5-2 parts of collagen, 6.5-7.6 parts of poly N-isopropylacrylamide, 0.5-0.7 parts of amino acid modified carboxymethyl chitosan, 0.1-0.2 parts of nano lithium ferrous silicate powder, 0.005-0.01 parts of antioxidant, and 80-90 parts of purified water.
[0009] Furthermore, the antioxidant is any one or more combinations of vitamin C, vitamin E and glutathione.
[0010] Furthermore, the collagen is any one of type I bovine Achilles tendon collagen, type II bovine cartilage collagen and type II bovine nasal membrane collagen.
[0011] Furthermore, amino acid modified carboxymethyl chitosan is prepared by the following steps:
[0012] The carboxymethyl chitosan and deionized water are stirred and mixed to obtain a carboxymethyl chitosan solution with a mass fraction of 1%; the amino acid is dissolved in deionized water to obtain an amino acid solution with a mass fraction of 4-6%, EDC hydrochloride, 4-dimethylaminopyridine, the amino acid solution and a newly configured 10% morpholineethanesulfonic acid aqueous solution are stirred and mixed and transferred to a reactor, and then the carboxymethyl chitosan solution is added to the reactor, and the reaction is carried out for 3-4 hours under magnetic stirring and 40-45° C., and the reaction solution is transferred to a dialysis bag with a dialysis molecular weight of 1000-3500Da after cooling to 20-25° C., and dialyzed with deionized water for 36-50 hours, and the dialyzate is decompressed and distilled to obtain a concentrated solution, and the concentrated solution is poured into a mixed solvent and allowed to stand for 12-24 hours, and the mixed solvent is removed by filtering after the precipitation is precipitated, and the precipitate is washed with anhydrous ethanol for 3-5 times, and vacuum dried at 40-50° C. to obtain amino acid modified carboxymethyl chitosan.
[0013] Furthermore, the usage ratio of carboxymethyl chitosan solution, amino acid solution, morpholineethanesulfonic acid aqueous solution, EDC hydrochloride and 4-dimethylaminopyridine is 10 mL: 5-6 mL: 5-6 mL: 0.24 g: 3.8 g.
[0014] Furthermore, the amino acid in the amino acid solution is glycine or alanine.
[0015] Furthermore, nano-lithium ferrous silicate powder is prepared by the following steps:
[0016] Add ferric nitrate nonahydrate and deionized water into a reaction kettle, stir for 15-30 minutes at 200-500 r / min, then add lithium acetate dihydrate into the reaction kettle and continue to stir for 15-30 minutes, then continue to stir for 20-40 minutes at 20-30° C., continuously add tetraethyl orthosilicate dropwise during the stirring process, then react at 80±5° C. for 20-24 hours, evaporate the water to obtain a gel, vacuum dry the gel, ball mill the gel, sieve through a 400-500 mesh sieve, put the ball milled powder into a crucible and transfer it to a tube furnace, heat the mixture to 650-700° C. at a rate of 3-5° C. / min under argon protection, keep the temperature for 12-16 hours, cool naturally, ball mill the product to a particle size of less than 1 μm, ultrasonically disperse the product with deionized water for 30-60 minutes, filter the product, wash the product with deionized water for 3-5 times, and dry the product to obtain nano lithium ferrous silicate powder.
[0017] Furthermore, the mass ratio of deionized water, ferric nitrate nonahydrate, lithium acetate dihydrate and tetraethyl orthosilicate is 25-30:2:1:5.3.
[0018] A method for preparing a collagen dressing with temperature-sensitive properties comprises the following steps:
[0019] Step 1: dissolving collagen and amino acid-modified carboxymethyl chitosan in purified water to obtain a mixed solution;
[0020] Step 2: Add poly (N-isopropylacrylamide), nano-lithium ferrous silicate powder and antioxidant to the mixed solution, and stir magnetically for 10-30 minutes under nitrogen protection to obtain a collagen dressing with temperature-sensitive properties.
[0021] Beneficial effects of the present invention:
[0022] The thermosensitive collagen dressing of the present invention has good mechanical properties after film formation, can meet the use requirements of areas with large activity such as skin outside joints, and the raw materials used have good biocompatibility and are non-irritating to the skin.
[0023] The amino acid-modified carboxymethyl chitosan in the raw material has good biocompatibility and biodegradability, which can increase the adhesion and stability of the dressing. After the carboxymethyl chitosan introduces positively charged amino acid groups on the surface, the solubility and biocompatibility of the carboxymethyl chitosan are further improved, and it helps to increase its antibacterial activity; glycine or alanine contains polar hydroxyl groups, which can form hydrogen bonds with the amino acid groups in collagen, increase the interaction between amino acid-modified carboxymethyl chitosan and collagen, and thus increase the mechanical properties of the dressing.
[0024] The nano-lithium ferrous silicate powder in the raw materials has good biocompatibility. As a polyanionic silicate, it can interact with the negative charge on the skin surface, increase the adhesion between the gel and the skin, and enable the dressing to better fit the skin surface: Nano-lithium ferrous silicate powder can interact electrostatically with amino groups, further promoting the cross-linking reaction between collagen molecules and amino acid-modified carboxymethyl chitosan molecules, thereby further increasing the strength and stability of the gel. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0027] Embodiment 1: This embodiment provides a collagen dressing with temperature-sensitive properties, comprising the following implementation steps:
[0028] Step 1: stir and mix carboxymethyl chitosan and deionized water to obtain a carboxymethyl chitosan solution with a mass fraction of 1%; dissolve alanine in deionized water to obtain an amino acid solution with a mass fraction of 4%; stir and mix 5L of a newly prepared 10% aqueous solution of morpholineethanesulfonic acid, 0.24kg of EDC hydrochloride, 3.8kg of 4-dimethylaminopyridine and 5L of the amino acid solution and transfer them to a reactor, then add 10L of the carboxymethyl chitosan solution to the reactor, react for 3h under magnetic stirring at 40°C to obtain a reaction solution.
[0029] Step 2: After cooling the reaction solution to 20°C, transfer the reaction solution to a dialysis bag with a dialysis molecular weight of 1000Da, dialyze with deionized water for 36 hours, and distill the dialyzate under reduced pressure to obtain a concentrated solution. Pour the concentrated solution into a mixed solvent and let it stand for 12 hours. After the precipitate is precipitated, filter and remove the mixed solvent. Wash the precipitate with anhydrous ethanol for 3 times, and vacuum dry it at 40°C to obtain amino acid modified carboxymethyl chitosan.
[0030] Step 3: Add 2kg of ferric nitrate nonahydrate and 25kg of deionized water to the reactor, stir at 200r / min for 15min, then add 1kg of lithium acetate dihydrate to the reactor and continue stirring for 15min, then continue stirring at 20°C for 20min, continuously add tetraethyl orthosilicate during the stirring process, add 5.3kg of tetraethyl orthosilicate in total, react at 80±5°C for 20h, evaporate the water to obtain a gel, vacuum dry the gel and then ball mill it, pass it through a 400-mesh sieve, put the ball-milled powder into a crucible and transfer it to a tubular furnace, heat it to 650°C at a rate of 3°C / min under argon protection and keep it warm for 12h, cool it naturally, ball mill the product to a particle size of <1μm, ultrasonically disperse it with deionized water for 30min, filter it, wash it 3 times with deionized water, and dry it to obtain nano-lithium ferrous silicate powder.
[0031] Step 4: Dissolve 1.5 g type I bovine Achilles tendon collagen and 0.5 g amino acid modified carboxymethyl chitosan in 80 g purified water to obtain a mixed solution, add 6.5 g poly (N-isopropylacrylamide), 0.1 g nano lithium ferrous silicate powder and 0.005 g vitamin C to the mixed solution, and stir magnetically for 10 minutes under nitrogen protection to obtain a collagen dressing with temperature-sensitive properties.
[0032] Embodiment 2: This embodiment provides a collagen dressing with temperature-sensitive properties, comprising the following implementation steps:
[0033] Step 1: stir and mix carboxymethyl chitosan and deionized water to obtain a carboxymethyl chitosan solution with a mass fraction of 1%; dissolve alanine in deionized water to obtain an amino acid solution with a mass fraction of 5%; stir and mix 5.5L of a newly prepared 10% aqueous solution of morpholineethanesulfonic acid, 0.24kg of EDC hydrochloride, 3.8kg of 4-dimethylaminopyridine and 5.5L of the amino acid solution and transfer them to a reactor, then add 10L of the carboxymethyl chitosan solution to the reactor, react for 3.5h under magnetic stirring and 42°C to obtain a reaction solution.
[0034] Step 2: After cooling the reaction solution to 22°C, transfer the reaction solution to a dialysis bag with a dialysis molecular weight of 2000Da, dialyze with deionized water for 40 hours, and distill the dialyzate under reduced pressure to obtain a concentrated solution. Pour the concentrated solution into a mixed solvent and let it stand for 16 hours. After the precipitate is precipitated, filter and remove the mixed solvent. Wash the precipitate with anhydrous ethanol for 4 times, and vacuum dry it at 45°C to obtain amino acid modified carboxymethyl chitosan.
[0035] Step 3: Add 2kg of ferric nitrate nonahydrate and 28kg of deionized water to the reactor, stir at 300r / min for 20min, then add 1kg of lithium acetate dihydrate to the reactor and continue stirring for 20min, then continue stirring at 25°C for 30min, continuously add tetraethyl orthosilicate during the stirring process, add 5.3kg of tetraethyl orthosilicate in total, react at 80±5°C for 22h, evaporate the water to obtain a gel, vacuum dry the gel and then ball mill it, pass it through a 450-mesh sieve, put the ball-milled powder into a crucible and transfer it to a tubular furnace, heat it to 680°C at a rate of 4°C / min under argon protection and keep it warm for 14h, cool it naturally, ball mill the product to a particle size of <1μm, ultrasonically disperse it with deionized water for 40min, filter it, wash it 4 times with deionized water, and dry it to obtain nano-lithium ferrous silicate powder.
[0036] Step 4: Dissolve 1.6 g of type II bovine nasal membrane collagen and 0.55 g of amino acid-modified carboxymethyl chitosan in 85 g of purified water to obtain a mixed solution, add 6.8 g of poly (N-isopropylacrylamide), 0.13 g of nano-lithium ferrous silicate powder and 0.008 g of vitamin E to the mixed solution, and stir magnetically for 20 minutes under nitrogen protection to obtain a collagen dressing with temperature-sensitive properties.
[0037] Embodiment 3: This embodiment provides a collagen dressing with temperature-sensitive properties, comprising the following implementation steps:
[0038] Step 1: stir and mix carboxymethyl chitosan and deionized water to obtain a 1% carboxymethyl chitosan solution; dissolve glycine in deionized water to obtain a 5% amino acid solution; stir and mix 5.5L of a newly prepared 10% aqueous solution of morpholineethanesulfonic acid, 0.24kg EDC hydrochloride, 3.8kg 4-dimethylaminopyridine and 5.5L of the amino acid solution and transfer them to a reactor, then add 10L of the carboxymethyl chitosan solution to the reactor, react for 3.5h under magnetic stirring and 42°C to obtain a reaction solution.
[0039] Step 2: After cooling the reaction solution to 22°C, transfer the reaction solution to a dialysis bag with a dialysis molecular weight of 3000Da, dialyze with deionized water for 45 hours, and distill the dialyzate under reduced pressure to obtain a concentrated solution. Pour the concentrated solution into a mixed solvent and let it stand for 20 hours. After the precipitate is precipitated, filter and remove the mixed solvent. Wash the precipitate with anhydrous ethanol for 4 times, and vacuum dry it at 45°C to obtain amino acid modified carboxymethyl chitosan.
[0040] Step 3: Add 2kg of ferric nitrate nonahydrate and 28kg of deionized water to the reactor, stir at 400r / min for 25min, then add 1kg of lithium acetate dihydrate to the reactor and continue stirring for 25min, then continue stirring at 25°C for 30min, continuously add tetraethyl orthosilicate during the stirring process, add 5.3kg of tetraethyl orthosilicate in total, react at 80±5°C for 22h, evaporate the water to obtain a gel, vacuum dry the gel and then ball mill it, pass it through a 450-mesh sieve, put the ball-milled powder into a crucible and transfer it to a tubular furnace, heat it to 680°C at a rate of 4°C / min under argon protection and keep it warm for 14h, cool it naturally, ball mill the product to a particle size of <1μm, ultrasonically disperse it with deionized water for 50min, filter it, wash it 4 times with deionized water, and dry it to obtain nano-lithium ferrous silicate powder.
[0041] Step 4: Dissolve 1.8 g of type II bovine cartilage collagen and 0.6 g of amino acid-modified carboxymethyl chitosan in 85 g of purified water to obtain a mixed solution, add 7.2 g of poly (N-isopropylacrylamide), 0.15 g of nano-lithium ferrous silicate powder and 0.008 g of glutathione to the mixed solution, and stir magnetically for 20 minutes under nitrogen protection to obtain a collagen dressing with temperature-sensitive properties.
[0042] Embodiment 4: This embodiment provides a collagen dressing with temperature-sensitive properties, comprising the following implementation steps:
[0043] Step 1: stir and mix carboxymethyl chitosan and deionized water to obtain a carboxymethyl chitosan solution with a mass fraction of 1%; dissolve glycine in deionized water to obtain an amino acid solution with a mass fraction of 6%; stir and mix 6L of a newly prepared 10% aqueous solution of morpholineethanesulfonic acid, 0.24kg of EDC hydrochloride, 3.8kg of 4-dimethylaminopyridine and 6L of the amino acid solution and transfer them to a reactor, then add 10L of the carboxymethyl chitosan solution to the reactor, react for 4h under magnetic stirring at 45°C to obtain a reaction solution.
[0044] Step 2: After cooling the reaction solution to 25°C, transfer the reaction solution to a dialysis bag with a dialysis molecular weight of 3500Da, dialyze with deionized water for 50 hours, and distill the dialyzate under reduced pressure to obtain a concentrated solution. Pour the concentrated solution into a mixed solvent and let it stand for 24 hours. After the precipitate is precipitated, filter and remove the mixed solvent. Wash the precipitate with anhydrous ethanol for 5 times, and vacuum dry it at 50°C to obtain amino acid modified carboxymethyl chitosan.
[0045] Step 3: Add 2kg of ferric nitrate nonahydrate and 30kg of deionized water to the reactor, stir at 500r / min for 30min, then add 1kg of lithium acetate dihydrate to the reactor and continue stirring for 30min, then continue stirring at 30°C for 40min, continuously add tetraethyl orthosilicate during the stirring process, add 5.3kg of tetraethyl orthosilicate in total, react at 80±5°C for 24h, evaporate the water to obtain a gel, vacuum dry the gel and then ball mill it, pass it through a 500-mesh sieve, put the ball-milled powder into a crucible and transfer it to a tubular furnace, heat it to 700°C at a rate of 5°C / min under argon protection and keep it warm for 16h, cool it naturally, ball mill the product to a particle size of <1μm, ultrasonically disperse it with deionized water for 60min, filter it, wash it with deionized water 5 times, and dry it to obtain nano-lithium ferrous silicate powder.
[0046] Step 4: Dissolve 2g type II bovine cartilage collagen and 0.7g amino acid modified carboxymethyl chitosan in 90g purified water to obtain a mixed solution, add 7.6g poly (N-isopropylacrylamide), 0.2g nano-lithium ferrous silicate powder and 0.01g antioxidant to the mixed solution, the antioxidant is a mixture of vitamin C, vitamin E and glutathione in a mass ratio of 2:2:1, and magnetically stir for 30 minutes under nitrogen protection to obtain a collagen dressing with temperature-sensitive properties.
[0047] Comparative Example 1: Based on Example 4, amino acid-modified carboxymethyl chitosan was not added, and the other steps remained unchanged to prepare a collagen dressing with thermosensitive properties.
[0048] Comparative Example 2: Based on Example 4, the amino acid-modified carboxymethyl chitosan was replaced with unmodified carboxymethyl chitosan, and the other steps remained unchanged to prepare a collagen dressing with thermosensitive properties.
[0049] Comparative Example 3: Based on Example 4, no nano lithium ferrous silicate powder was added, and the other steps remained unchanged to prepare a collagen dressing with temperature-sensitive properties.
[0050] Performance tests were performed on Examples 1 to 4 and Comparative Examples 1 to 3. Different collagen dressings were thinly coated on a 37°C insulation plate (simulating human skin temperature), with the coating thickness kept consistent, and the time required for film formation was tested; the phase transition temperature of different collagen dressings was tested using a Shengbao Technology RH-20 rotational rheometer; different collagen dressings were dried to prepare strip samples with a thickness of 1 mm, a width of 4 mm and a length of 16 mm, and both ends of the strip samples were glued to the fixture of a universal mechanical testing machine with glue, and the tensile strength and elongation at break were tested at a tensile speed of 20 mm / min at 25°C, and the average value of three times was taken; different dressing films with a thickness of 1 mm were taken, and an antibacterial test was performed with reference to the antibacterial (inhibition) test method in 2.1.7 of the Technical Specifications for Disinfection (2008 Edition), and the diameter of the antibacterial ring was recorded; the results are shown in Table 1:
[0051]
[0052] As can be seen from Table 1, the tensile strength at break and elongation at break of the collagen dressings in Examples 1 to 4 are higher, and amino acid-modified carboxymethyl chitosan and nano-lithium ferrous silicate powder help to increase their mechanical properties; amino acid-modified carboxymethyl chitosan helps to increase the antibacterial properties of the collagen dressing.
[0053] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A collagen dressing with thermosensitive properties, characterized in that: The following raw materials are included by mass: 1.5-2 parts of collagen, 6.5-7.6 parts of poly N-isopropylacrylamide, 0.5-0.7 parts of amino acid modified carboxymethyl chitosan, 0.1-0.2 parts of nano-lithium ferrous silicate powder, 0.005-0.01 parts of antioxidant, and 80-90 parts of purified water; The amino acid modified carboxymethyl chitosan is prepared by the following steps: The carboxymethyl chitosan and deionized water are stirred and mixed to obtain a carboxymethyl chitosan solution with a mass fraction of 1%; the amino acid is dissolved in deionized water to obtain an amino acid solution with a mass fraction of 4-6%, EDC hydrochloride, 4-dimethylaminopyridine, the amino acid solution and a newly configured 10% morpholineethanesulfonic acid aqueous solution are stirred and mixed and transferred to a reactor, and then the carboxymethyl chitosan solution is added to the reactor, and the reaction is carried out for 3-4 hours under magnetic stirring and 40-45° C., and the reaction solution is transferred to a dialysis bag with a dialysis molecular weight of 1000-3500Da after cooling to 20-25° C., and dialyzed with deionized water for 36-50 hours, and the dialyzate is decompressed and distilled to obtain a concentrated solution, and the concentrated solution is poured into a mixed solvent and allowed to stand for 12-24 hours, and the mixed solvent is removed by filtering after the precipitation is precipitated, and the precipitate is washed with anhydrous ethanol for 3-5 times, and vacuum dried at 40-50° C. to obtain amino acid modified carboxymethyl chitosan.
2. The collagen dressing with temperature-sensitive properties according to claim 1, characterized in that: The antioxidant is a combination of any one or more of vitamin C, vitamin E and glutathione mixed in any ratio.
3. The collagen dressing with temperature-sensitive properties according to claim 1, characterized in that: The collagen is any one of type I bovine Achilles tendon collagen, type II bovine cartilage collagen and type II bovine nasal membrane collagen.
4. The collagen dressing with temperature-sensitive properties according to claim 1, characterized in that: The dosage ratio of the carboxymethyl chitosan solution, the amino acid solution, the morpholineethanesulfonic acid aqueous solution, EDC hydrochloride and 4-dimethylaminopyridine is 10 mL: 5-6 mL: 5-6 mL: 0.24 g: 3.8 g.
5. The collagen dressing with thermosensitive properties according to claim 1, characterized in that: The nano lithium ferrous silicate powder is prepared by the following steps: Add ferric nitrate nonahydrate and deionized water into a reaction kettle, stir for 15-30 minutes at 200-500 r / min, then add lithium acetate dihydrate into the reaction kettle and continue to stir for 15-30 minutes, then continue to stir for 20-40 minutes at 20-30° C., continuously add tetraethyl orthosilicate dropwise during the stirring process, then react at 80±5° C. for 20-24 hours, evaporate the water to obtain a gel, vacuum dry the gel, ball mill the gel, sieve through a 400-500 mesh sieve, put the ball milled powder into a crucible and transfer it to a tube furnace, heat the mixture to 650-700° C. at a rate of 3-5° C. / min under argon protection, keep the temperature for 12-16 hours, cool naturally, ball mill the product to a particle size of less than 1 μm, ultrasonically disperse the product with deionized water for 30-60 minutes, filter the product, wash the product with deionized water for 3-5 times, and dry the product to obtain nano lithium ferrous silicate powder.
6. The collagen dressing with temperature-sensitive properties according to claim 5, characterized in that: The mass ratio of the deionized water, ferric nitrate nonahydrate, lithium acetate dihydrate and tetraethyl orthosilicate is 25-30:2:1:5.
3.
7. The collagen dressing with thermosensitive properties according to claim 1, characterized in that: The amino acid in the amino acid solution is glycine or alanine.
8. The method for preparing the collagen dressing with temperature-sensitive properties according to any one of claims 1 to 7, characterized in that: The steps include: Step 1: dissolving collagen and amino acid-modified carboxymethyl chitosan in purified water to obtain a mixed solution; Step 2: Add poly (N-isopropylacrylamide), nano-lithium ferrous silicate powder and antioxidant to the mixed solution, and stir magnetically for 10-30 minutes under nitrogen protection to obtain a collagen dressing with temperature-sensitive properties.
Citation Information
Patent Citations
Recombinant collagen and its thermosensitive hydrogel
CN107540744B
Collagen dressing with temperature-sensitive properties and preparation method thereof
CN105363063A
Injectable and degradable thermo-sensitive hydrogel and preparation method thereof
CN105664250A